Health beliefs and attitudes toward Influenza and COVID-19 vaccination in Portugal: a study using a mixed-method approach - Santos, Ana João; Kislaya, Irina; Matias-Dias, Carlos; Machado, Ausenda (Frontiers in Public Health, 2024)
Vaccination is one of the most effective population strategies to prevent infectious diseases and mitigate pandemics, and it is important to understand vaccine uptake determinants, since vaccine hesitancy has been increasing for the past few decades. The Health Belief Model (HBM) has been widely used for understanding vaccination behaviour. The current study aimed to assess influenza (IV) non-uptake and attitude towards COVID-19 vaccination, two important respiratory diseases with similar symptoms, and routes of transmission, in the Portuguese population. We conducted a cross-sectional study using a panel sample of randomly chosen Portuguese households. A total of 1050 individuals aged 18 years responded to a telephone or online questionnaire. Through a mixed method approach we employed thematic content analysis to describe reasons for not taking IV considering the HBM dimensions, and quantitative statistical analysis to estimate IV and COVID-19 vaccine coverage. IV uptake for the overall population was 30.7% (CI95%: 26.5, 35.2). Susceptibility as a main factor for IV non-uptake, followed by barriers, such as stock availability and fear of adverse effects. The uptake of the COVID-19 was very high in the study population (83.1%,95%CI: 13.6% to 20.9%). There was a high perception of the COVID-19 associated severity and fear from the consequences. Individuals that reported IV uptake seemed to perceive a higher severity from the COVID-19 and a higher benefit of taking the COVID-19 vaccine for the severe complications. The population does not seem to consider influenza to be a health risk, in opposition to COVID-19, that was considered to be a possible severe disease. The association between IV uptake and COVID-19 perceptions, highlights that an overall attitude towards vaccination in general may be an important individual determinant.